Birth preparedness among women attending antenatal care clinic in health facilities within Bureti Sub County of Kericho county, Kenya - Kerubo, Omari P.; Yaw, Afrane; Ouma, Peter (JOOUST, 2015)
Maternal mortality remains a major public health problem in Kenya with 488 deaths per 100,000 live births. Birth preparedness and complication readiness is one of the recommended strategies by the major global initiatives and implemented by the Kenyan government to reduce maternal mortality. It is the process of planning for normal birth and anticipating the actions needed in case of an emergency during pregnancy, delivery and post-partum period. Little is known about the status of Birth Preparedness of pregnant women in Kenya especially those in rural regions. The study aimed at assessing Birth Preparedness and Complication Readiness and the associated factors among women attending antenatal care clinic (ANC) at health facilities within Bureti Sub County. A facility based cross sectional study was carried out among pregnant women attending health facilities within the Sub County. Results from 149 respondents showed that large proportion of the women 70.5 % (n=105) were prepared for birth while 90.6% (n=135) reported readiness for complications. Majority of the respondents 87.9% (n= 139) had identified a place of delivery, 72.5 % (n=108) knew the expected date of delivery. Only 4.7% of the respondents were able to mention at least two danger signs in all the three phases namely pregnancy, delivery, and post-partum. Vaginal bleeding was most mentioned danger sign in all the three phases. Women who recognized vaginal bleeding as a danger sign in pregnancy were 3 times more likely to be prepared for birth than those who did not know (OR=3.00, p=0.004). Knowledge of vaginal bleeding was also associated with complication readiness (OR=3.47, p=0.046). The study revealed that a greater proportion of women attending ANC clinic within Bureti Sub County were well prepared for birth and ready for obstetric complications. However, the low awareness of obstetric danger signs may lead to the first and second delays in seeking health care during obstetric emergencies. It is important therefore to intensify ANC health education on obstetric danger signs to all women attending ANC irrespective of their demographic characteristics.
1st JOOUST Scientific Conference